Análisis comparativo de modelos digitales de terreno obtenidos por tecnología lidar con aeronave no tripulada y por fotogrametría con UAV en zona de montaña (2022)
The current document exposes the significant differences obtained when comparing a Digital Terrain Model obtained from a LIDAR Sensor carried by an unmanned aircraft and a Digital Terrain Model obtained from UAV Photogrammetry. Although the technologies that are exposed are similar, they do not yield the same results in a product DTM. A comparison of DTM is made in a rural area that presents mountainous topographic conditions, with the presence of forest and the second study area is an urban space corresponding to a main road located in the city of Bogotá, it is characterized by the great level of detail that surrounds it, for expose the advantages and disadvantages of each one and suggest some fields of implementation of the same